The Seasonal Dynamics and the Influence of Human Activities on Campus Outdoor Microbial Communities - Chen, Chaoyun; He, Ruiqiao; Cheng, Zhangyu; Han, Maozhen; Zha, Yuguo; Yang, Pengshuo; Yao, Qi; Zhou, Hao; Zhong, Chaofang; Ning, Kang (Frontiers in Microbiology, 2019)
Large scale campus resembles a small ‘semi-open community’, harboring disturbances from the exchanges of people and vehicles, wherein stressors such as temperature and population density differ among the ground surfaces of functional partitions. Therefore, it represents a special ecological niche for the study on microbial ecology in the process of urbanization. In this study, we investigated outdoor microbial communities in four campuses in Wuhan, China. We obtained 284 samples from 55 sampling sites over 6 seasons, as well as their matching climatic and environmental records. The structure of campus outdoor microbial communities which influenced by multiple climatic factors featured seasonality. The dispersal influence of human activities on microbial communities also contributed to this seasonal pattern non-negligibly. However, despite the microbial composition alteration in response to multiple stressors, the overall predicted function of campus outdoor microbial communities remained stable across campuses. The spatial-temporal dynamic patterns on campus outdoor microbial communities and its predicted functions have bridged the gap between microbial and macro-level ecosystems, and provided hints towards a better understanding of the effects of climatic factors and human activities on campus micro-environments.